Penguatan Branding Produk Matcha Kaze melalui Strategi Integrated Marketing Communication - Jacklyn Wongsodiredjo; Monika Teguh (JKOMDIS : Jurnal Ilmu Komunikasi Dan Media Sosial, 2026)
Matcha has become one of the most popular culinary products among consumers. With the increasing trend of matcha consumption, the number of matcha-based culinary businesses has also continued to grow. This has led to competition that must be faced, one of which is by strengthening branding and marketing communication efforts. Kaze Matcha, as one of the matcha-based culinary entrepreneurs, has successfully built a strong brand identity and awareness through the implementation of an integrated marketing communication strategy. Based on this phenomenon, this study aims to describe the role of integrated marketing communication in strengthening Kaze Matcha's product branding. The research method used is descriptive qualitative, with interviews, observations, and document studies as data collection methods. The results of the study show that the application of IMC combined with digital marketing strategies, such as the use of Meta Ads and participation in various offline events, has proven to be effective in expanding brand reach while building direct engagement with consumers. Collaboration with communities and F&B MSMEs has also strengthened the brand's creative, authentic, and adaptive character to market trends. This study also shows that the implementation of IMC strategies, digital marketing, and collaboration has been proven to increase brand awareness to the point of brand recall. Therefore, this study can also be used by Kaze Matcha and other matcha-based culinary entrepreneurs to develop more specific strategies to increase engagement and brand awareness in the future.